Donor/recipient ascending aortic diameter ratio as a novel potential metric for donor selection and improved clinical outcomes in heart transplantation: a propensity score-matched study - Masroor, Matiullah; Chen, Yuqi; Wang, Yixuan; Dong, Nianguo (Frontiers in Cardiovascular Medicine, 2023)
Background Donor/recipient size matching is paramount in heart transplantation. Body weight, height, body mass index, body surface area, and predicted heart mass (PHM) ratios are generally used in size matching. Precise size matching is important to achieve better clinical outcomes. This study aims to determine the donor/recipient ascending aortic diameter (AAoD) ratio as a metric for donor selection and its effect on postoperative clinical outcomes in heart transplant patients. Methods We retrospectively reviewed all consecutive patients who underwent heart transplantation from January 2015 to December 2018. A cutoff value of 0.8032 for the donor/recipient AAoD ratio (independent variable for the primary endpoint during unmatched cohort analysis) was determined for predicting in-hospital mortality. The patients were divided into two groups based on the cutoff value. Group A, AAoD < 0.8032 (n = 96), and Group B, AAoD > 0.8032 (n = 265). A propensity score-matched (PSM) study was performed to equalize the two groups comprising 77 patients each in terms of risk. A Cox regression model was developed to identify the independent preoperative variables affecting the primary end-point. The primary endpoint was all-cause in-hospital mortality. Results A total of 361 patients underwent heart transplantation during the given period. On the multivariate analysis, donor/recipient PHM ratio [HR 16.907, 95% confidence interval (CI) 1.535–186.246, P = 0.021], donor/recipient AAoD ratio < 0.8032 (HR 5.398, 95% CI 1.181–24.681, P = 0.030), and diabetes (HR 3.138, 95% CI 1.017–9.689, P = 0.047) were found to be independent predictors of in-hospital mortality. Group A had higher 3-year mortality than Group B (P = 0.022). The surgery time was longer and postoperative RBC, plasma, and platelets transfusion were higher in Group A (P < 0.05). Although not statistically significant the use of continuous renal replacement therapy (P = 0.054), and extracorporeal membrane oxygenation (P = 0.086), was realatively higher, and ventilation time (P = 0.079) was relatively longer in Group A. Conclusions The donor/recipient AAoD ratio is a potential metric for patient matching and postoperative outcomes in heart transplantation. A donor/recipient AAoD ratio > 0.8032 could improve post-heart transplantation outcomes and donor heart utilization.